Sufism in the contemporary art of Malaysia / Dr. Ahmadrashidi Hasan and Dr. Mizan Hitam - Hasan, Ahmadrashidi; Hitam, Mizan (Faculty of Art and Design, 2012)
Sufism is the higher thought of Islam that venture into the domain of spirituality (bathin). It involved the perfection of the practice (al-syari 'ah) process of the path (al-tariqah), the ideology of the truth (al-haqiqah), the philosophy of the knowing (al-makrifah). The knowing (al-makrifah) involved the process of unifying to gain the unity of practice (tauhidul afal), the unity of character (tauhidul sifat), unity in name (tauhidul asma) and the unifying of the essence (tauhidul Dzat) with the only existing essence (Dzat wajibal wujud). The nobility of the ideology (haat) and the beauty of the experience (zauq) of sufism si only felt among its practitioner. This paper disclosed some of the artists who observed to express Sufism , both ideological and experiential. It discussed the content analysis of their artworks on aspects like image, subject and their meaning from the perspectives of Sufism and also the formalistic aspects which involved the style and visuals. Artists appeared to used the implicit manifestation of expression which involved metaphorical and abstract representation . It is established that there are artists in Malaysia who expressed the ideology of Sufism or expressed the beauty of the spiritual experience of the Sufism.